PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP RESILIENSI PADA PENGGUNA NARKOBA DIYAYASAN MITRA MULIA BANYUASIN - Merry Ariani; Sawi Sujarwo (Journal of Innovation Research and Knowledge, 2024)
This research aims to investigate the effect of Spiritual Emotional Freedom Technique (SEFT) therapy on increasing resilience in drug users at the Mitra Mulia Banyuasin Foundation. This research aims to understand whether the application of SEFT can help drug users develop the ability to bounce back from difficulties, overcome stress, manage negative emotions, and maintain motivation in their recovery process. Thus, this research aims to fill the knowledge gap in the literature regarding the effectiveness of SEFT as a rehabilitation method for drug users, as well as contribute to the development of more holistic and sustainable recovery strategies for those involved in drug abuse problems. The total population in this study was 8 people used as samples. The sampling technique uses purposive sampling technique. The measuring instrument used in this research is the Likert scale. The analysis technique uses validity tests and reliability tests. The results of this study show that the treatment applied as a whole had a positive impact on increasing the subjects' resilience scores, with an average increase from pretest to posttest. However, the effectiveness of treatment varied between subjects